Curable composition and cured product
Patent Information
- Application Number
- KR1020237032922
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-01-26
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2042-01-26
Smart Images

Figure 112023106055332-PCT00001 
Figure 112023106055332-PCT00002 
Figure 112023106055332-PCT00003
Abstract
Description
Technology Field
[0001] The present disclosure relates to a curable composition and a cured product. Background Technology
[0002] Recently, there has been a significant improvement in the performance of electronic devices such as PCs, mobile phones, and personal digital assistants (PDAs), as well as lighting and display devices such as light-emitting diodes (LEDs) and electroluminescent (ELs). This is due to the significant performance improvement of computing elements and light-emitting elements. As the performance of computing elements and light-emitting elements improves, the amount of heat generated also increases significantly, making heat dissipation in electronic devices, lighting, and display devices a critical issue. As a heat countermeasure, measures are being taken to install Thermal Interface Materials (TIMs) between the heating element and the heat sink to transfer the heat generated by the computing element or light-emitting element to the heat sink without loss and to dissipate the heat through the heat sink. Thermal sheets, thermally conductive grease, and gap fillers are known to be commonly used as TIMs, and gap fillers, which are initially in a paste state and harden into a solid after application, are attracting attention.
[0003] As a gap filler having excellent flexibility, shape stability and thermal conductivity, for example, International Publication No. 2020 / 149193 discloses a curable composition comprising a compound (A) having one (meth)acrylate group in one molecule, a compound (B) having two or more (meth)acrylate groups in one molecule, a polymerization initiator (C), a dispersant (D), and a thermally conductive filler (E) comprising zinc oxide. The problem to be solved
[0004] The problem to be solved by one embodiment of the present disclosure is to provide a curable composition with excellent oil-repellent properties.
[0005] The problem to be solved by another embodiment of the present disclosure is to provide a cured product made of a curable composition with excellent oil-reducing properties.
[0006] Herein, "detachment" in the present disclosure means that, in the pre-curing curable composition related to the present disclosure, separation between the thermally conductive filler and the liquid component contained in the curable composition is suppressed as time elapses. means of solving the problem
[0007] The present disclosure includes the following embodiments.
[0008] <1> A thermally conductive filler (A) comprising at least one selected from the group consisting of a thermally conductive filler A having a volume average particle diameter of 0.3㎛ or more and less than 1㎛ and a thermally conductive filler B having a volume average particle diameter of 1㎛ or more and less than 10㎛, and a thermally conductive filler C having a volume average particle diameter of 10㎛ or more and 15㎛ or less, and
[0009] A monomer (B) having a (meth)acryloyl group, and
[0010] polymerization initiator (C) and,
[0011] It includes a dispersant (D),
[0012] Based on the total mass of the above thermally conductive filler (A), the content X of the above thermally conductive filler A is 0 mass% to 40 mass%, the content Y of the above thermally conductive filler B is 0 mass% to 40 mass%, and the content Z of the above thermally conductive filler C is 20 mass% to 60 mass% (provided that both content X and content Y are not 0 mass%),
[0013] Curable composition.
[0014] <2> The above thermally conductive filler (A) comprises at least one selected from zinc oxide, magnesium oxide, and aluminum oxide, <1> Curable composition described in
[0015] <3> The above thermally conductive filler (A) comprises zinc oxide, <2> Curable composition described in
[0016] <4> The above thermal conductive filler (A) is a surface-treated thermal conductive filler, <1> inside <3> A curable composition described in any one of the following.
[0017] <5> The above monomer (B) comprises a compound represented by the following formula (1). <1> inside <4> A curable composition described in any one of the following.
[0018] <Painting 1>
[0019]
[0020] R in the above equation (1) 1 represents an alkyl group having 1 to 50 carbon atoms, and R 2 represents a hydrogen atom or a methyl group.
[0021] <6> The above monomer (B) comprises a compound represented by the following formula (2). <1> inside <5> A curable composition described in any one of the following.
[0022] <Painting 2>
[0023]
[0024] R in the above equation (2) B1 represents an alkylene group having 1 to 5 carbon atoms, and R B2 and R B3 Each represents an independent hydrogen atom or a methyl group, and n represents an integer greater than or equal to 4.
[0025] <7> <1> inside <6> A cured product by a curable composition described in any one of the following. Effects of the invention
[0026] According to one embodiment of the present disclosure, a curable composition with excellent oil-reducing properties is provided.
[0027] According to another embodiment of the present disclosure, a cured product of a curable composition with excellent oil-repellent properties is provided. Specific details for implementing the invention
[0028] Hereinafter, a curable composition and a cured product related to the present disclosure will be described in detail.
[0029] In the present disclosure, '~' indicating a numerical range represents a range that includes the values listed as the upper and lower limits, respectively. Furthermore, if only the upper limit of a numerical range indicated by '~' has a unit listed, it means that the lower limit also has the same unit.
[0030] In this disclosure, the content or content of each component in the composition refers to the total content or content of the corresponding multiple substances present in the composition, unless specifically stated otherwise, in cases where multiple substances corresponding to each component exist within the composition.
[0031] In numerical ranges described stepwise in the present disclosure, an upper or lower limit value described in any numerical range may be substituted with an upper or lower limit value of a numerical range described stepwise.
[0032] In the numerical ranges described in this disclosure, any upper or lower limit value described in any numerical range may be replaced with the values presented in the embodiments.
[0033] In the present disclosure, "(meth)acryl" is a term used as a concept including both acrylic and methacryl, and "(meth)acryloyl" is a term used as a concept including both acryloyl and methacryloyl.
[0034] In the present disclosure, 'mass%' and 'weight%' are synonyms, and 'parts of mass' and 'parts of weight' are synonyms.
[0035] In the present disclosure, each component in the composition refers to the total amount of the plurality of substances present in the composition, where each component is present in multiple quantities in the composition, unless specifically stated otherwise.
[0036] In the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment.
[0037] In this disclosure, 'JIS' is an abbreviation for Japanese Industrial Standards.
[0038] (Curing composition)
[0039] The curable composition related to the present disclosure comprises a thermally conductive filler (A) comprising at least one selected from the group consisting of a thermally conductive filler A having a volume average particle diameter of 0.3 μm or more and less than 1 μm and a thermally conductive filler B having a volume average particle diameter of 1 μm or more and less than 10 μm, and a thermally conductive filler C having a volume average particle diameter of 10 μm or more and 15 μm or less, a monomer (B) having a (meth)acryloyl group, a polymerization initiator (C), and a dispersant (D), wherein, based on the total mass of the thermally conductive filler (A), the content X of the thermally conductive filler A is 0 mass% to 40 mass%, the content Y of the thermally conductive filler B is 0 mass% to 40 mass%, and the content Z of the thermally conductive filler C is 20 mass% to 60 mass%. However, both the content X and the content Y are not necessarily 0 mass%.
[0040] The curable composition related to the present disclosure has excellent oil-reducing properties by having the above composition.
[0041] In addition, below, thermally conductive filler A with a volume average particle diameter of 0.3 μm or more and less than 1 μm, thermally conductive filler B with a volume average particle diameter of 1 μm or more and less than 10 μm, and thermally conductive filler C with a volume average particle diameter of 10 μm or more and less than 15 μm are each simply referred to as thermally conductive filler A, thermally conductive filler B, and thermally conductive filler C.
[0042] Curable compositions containing solid particles, such as thermally conductive fillers, are required to possess downward flow properties over time from preparation until they are provided for use (e.g., when stored). In curable compositions with poor downward flow properties, the thermally conductive filler may settle, requiring stirring during use, or a concentration gradient of the thermally conductive filler may occur within the storage container (e.g., syringe), which may result in the inability to obtain the desired viscosity or thermal conductivity and impair the uniformity of the application amount or quality stability.
[0043] In addition, when the content ratio of thermally conductive fillers with medium and large particle diameters (e.g., a volume average particle diameter of 10 μm or more) is high in the curable composition, the thermal conductivity increases, but the thermally conductive fillers tend to settle easily, and the oil-down performance tends to deteriorate. When the content ratio of thermally conductive fillers with medium and large particle diameters is reduced, the oil-down performance improves, but the thermal conductivity tends to decrease.
[0044] In this regard, the curable composition related to the present disclosure comprises at least one selected from the group consisting of thermal conductive filler A and thermal conductive filler B as a thermal conductive filler (A), and thermal conductive filler C, and it is presumed that the oil-draining properties are excellent by setting the content of thermal conductive filler A X, the content of thermal conductive filler B Y, and the content of thermal conductive filler C Z to a predetermined range.
[0045] In addition, the curable composition related to the present disclosure may have excellent thermal conductivity (specifically 3 W / m·K or higher). This is presumed to be because the thermally conductive filler (A) is included in the composition, and more specifically, because the thermally conductive filler C is included in a ratio of content Z.
[0046] Furthermore, the curable composition related to the present disclosure may have a viscosity suitable for use (e.g., for gap filler use). This is presumed to be because the thermally conductive filler (A) is included in the composition, and more specifically, because the thermally conductive fillers A and B are included in a ratio of content Y and content Z, respectively.
[0047] Hereinafter, each component of the curable composition related to the present disclosure will be described.
[0048] <Thermal conductive filler (A)>
[0049] The curable composition related to the present disclosure contains a thermally conductive filler (A).
[0050] The thermally conductive filler (A) comprises at least one selected from the group consisting of thermally conductive filler A with a volume average particle diameter of 0.3 μm or more and less than 1 μm, and thermally conductive filler B with a volume average particle diameter of 1 μm or more and less than 10 μm, and thermally conductive filler C with a volume average particle diameter of 10 μm or more and 15 μm or less.
[0051] Thermally conductive filler A, thermally conductive filler B, and thermally conductive filler C may each be one type of thermally conductive filler having a predetermined volume average particle diameter, or two or more types of thermally conductive fillers having a predetermined volume average particle diameter.
[0052] The volume average particle diameter of thermally conductive filler A is 0.3㎛ or more and less than 1㎛ from the perspective of oil flow, and is preferably 0.4㎛ to 0.8㎛.
[0053] The volume average particle diameter of thermally conductive filler B is 1 µm or more and less than 10 µm from the perspective of oil flow, and is preferably 3 µm to 6 µm.
[0054] The volume average particle diameter of the thermally conductive filler C is 10㎛ to 15㎛ in terms of oilability and thermal conductivity, and 11㎛ to 13㎛ is preferred.
[0055] The volume average particle diameter of the thermally conductive filler is measured by the laser diffraction and scattering method in accordance with JIS Z 8825:2013 (corresponding international standard: ISO 13320).
[0056] Specifically, the volume distribution of thermally conductive filler particles is measured using a laser diffraction scattering particle size measuring device for a sample containing thermally conductive filler particles. Based on the obtained measurements (volume distribution), the volume-averaged particle diameter of the thermally conductive filler contained in the sample can be determined.
[0057] An example of a laser diffraction scattering particle size measuring device is the SALD-7500nano nano-particle diameter distribution measuring device manufactured by Shimadzu Corporation.
[0058] Whether the curable composition contains a thermally conductive filler belonging to any one of thermally conductive filler A, thermally conductive filler B, or thermally conductive filler C can be confirmed by a laser diffraction scattering particle size analyzer.
[0059] Specifically, it can be verified using the following methods.
[0060] The thermally conductive filler is isolated by removing components other than the thermally conductive filler from the curable composition. The volume distribution of a measurement sample prepared from the isolated thermally conductive filler is measured using a laser diffraction scattering particle size analyzer. Based on the measurement results, the presence or absence of filler particles within the particle diameter range of thermally conductive filler A, thermally conductive filler B, or thermally conductive filler C is confirmed. The removal of components other than the thermally conductive filler is carried out by the following method.
[0061] - Removal of ingredients other than thermally conductive fillers -
[0062] The curable composition is dissolved in a solvent that does not dissolve thermally conductive fillers, such as hexane, and then centrifuged. By repeating the above process three or more times, the thermally conductive filler and other components are separated.
[0063] The obtained thermally conductive filler is dried in a constant temperature bath at 150°C for 90 minutes to remove residual solvent.
[0064] If catalog values can be verified for the volume-averaged particle diameter of the thermally conductive filler, the catalog values are adopted.
[0065] The thermal conductive filler A and the thermal conductive filler B included in the thermal conductive filler (A) may be either one or both. From the perspective of oil flow, it is preferable that the thermal conductive filler (A) includes both the thermal conductive filler A and the thermal conductive filler B.
[0066] The content of thermal conductive filler A X, the content of thermal conductive filler B Y, and the content of thermal conductive filler C Z can be confirmed by calculating the content ratios of thermal conductive filler A, thermal conductive filler B, and thermal conductive filler C based on the measurement results of the particle diameter distribution of thermal conductive filler (A) obtained from a laser diffraction scattering particle size measuring device.
[0067] The content X of the thermally conductive filler A is 0% to 40% by mass based on the total mass of the thermally conductive filler (A), 20% to 35% by mass is preferred, and 25% to 30% by mass is more preferred.
[0068] The content Y of the thermally conductive filler B is 0% to 40% by mass based on the total mass of the thermally conductive filler (A), 10% to 30% by mass is preferred, and 15% to 25% by mass is more preferred.
[0069] The content Z of the thermally conductive filler C is 20% to 60% by weight based on the total mass of the thermally conductive filler (A). The content Z can be, for example, 40% to 60% by weight.
[0070] When the thermally conductive filler (A) includes both thermally conductive filler A and thermally conductive filler B, the content ratio [A:B] of thermally conductive filler A and thermally conductive filler B is preferably 30:70 to 80:20 by mass, more preferably 50:50 to 70:30, and even more preferably 55:45 to 65:35 in terms of oil flow.
[0071] The content ratio [(A+B):C] of thermal conductive filler A, thermal conductive filler B, and thermal conductive filler C is preferably 40:60 to 60:40 by mass and more preferably 45:55 to 55:45 in terms of thermal conductivity and thermal conductivity.
[0072] The material of the thermally conductive filler (A) is not particularly limited and may include zinc oxide, magnesium oxide, aluminum oxide, boron nitride, aluminum nitride, carbon, etc. It is preferable to include at least one selected from zinc oxide, magnesium oxide, and aluminum oxide in terms of oil resistance, insulation, high thermal conductivity, and performance as a thermally conductive filler, and zinc oxide is more preferable.
[0073] In some embodiments, the thermally conductive filler (A) preferably contains only thermally conductive fillers A, B, and C in terms of oil-draining properties, and it is more preferable that all of the thermally conductive fillers A, B, and C are zinc oxide in terms of oil-draining properties, viscosity, and high thermal conductivity.
[0074] The thermally conductive filler (A) may be a surface-treated thermally conductive filler. The surface-treated thermally conductive filler can improve affinity with other contained components other than the thermally conductive filler, thereby contributing to improved oiliness, low viscosity, and thermal conductivity.
[0075] Surface treatment for thermally conductive fillers is not particularly limited and may be physical or chemical treatment, and known treatments capable of treating the surface of the particles constituting the thermally conductive filler may be applied.
[0076] As for the surface treatment, it is preferable to use a surface treatment agent.
[0077] Examples of surface treatment agents include silane-based coupling agents, titanium-based coupling agents, carboxylic acid-based coupling agents, phosphate-based coupling agents, fatty acids, polymer compounds, surfactants, and oils.
[0078] From the perspective of dispersibility, it is preferable that the thermally conductive filler (A) be surface-treated using a silane-based coupling agent as a surface treatment agent.
[0079] Thermal conductive fillers A, B, and C may all be surface-treated thermal conductive fillers, or any one of them may be a surface-treated thermal conductive filler. From the perspective of oil resistance and thermal conductivity, it is preferable to contain at least a surface-treated thermal conductive filler as thermal conductive filler C.
[0080] -content-
[0081] The content of the thermally conductive filler (A) is preferably 80 mass% or more with respect to the total mass of the composition, more preferably 85 mass% to 98 mass%, and even more preferably 90 mass% to 96 mass%.
[0082] In addition, the content of the thermally conductive filler (A) is preferably 40 volume% or more with respect to the total volume of the composition, more preferably 47 volume% to 80 volume%, and even more preferably 60 volume% to 80 volume%.
[0083] The thermal conductivity of the filler (A) can be further improved by having the above range of content.
[0084] <Monomer (B) having (meta)acryloyl groups>
[0085] A curable composition related to the present disclosure comprises a monomer (B) having a (meth)acryloyl group. The monomer (B) having a (meth)acryloyl group may be a monomer having one (meth)acrylate group in one molecule, or a monomer having two or more (meth)acrylate groups in one molecule.
[0086] Monomers having one (meth)acrylate group in one molecule are not particularly limited and examples include straight-chain, branched-chain, or cyclic alkyl (meth)acrylates, acrylic acid, etc.
[0087] In terms of achieving a balance of heat resistance and flexibility, the monomer having one (meth)acrylate group in one molecule is preferably a straight-chain or branched-chain alkyl (meth)acrylate, and it is even more preferable to include a compound represented by the following formula (1).
[0088] <Painting 3>
[0089]
[0090] R in the above equation (1) 1 represents an alkyl group having 1 to 50 carbon atoms, and R 2 represents a hydrogen atom or a methyl group.
[0091] Among the above formula (1), R 1 The alkyl group in this case may be straight-chain or branched. Also, the alkyl group may have substituents.
[0092] Examples of substituents include carboxyl groups, hydroxyl groups, amino groups, aryl groups, heterocyclic groups, etc., and it is preferable that they be carboxyl groups or hydroxyl groups, and more preferable that they be hydroxyl groups.
[0093] R in terms of the compatibility of heat resistance and flexibility 1 In the above, the total number of carbon atoms of the alkyl group is preferably 2 to 30, more preferably 5 to 25, even more preferably 10 to 25, and particularly preferably 12 to 24.
[0094] Here, the total number of carbon atoms refers to the total number of carbon atoms including the number of carbon atoms of the substituent when the alkyl group has a substituent containing carbon atoms.
[0095] R in Equation (1) in terms of the compatibility of heat resistance and flexibility 1It is preferable that the alkyl group has a total of 2 to 30 carbon atoms and is straight or branched or has a substituent, more preferable that it has a total of 2 to 25 carbon atoms and is straight or branched or has a hydroxyl group, and more preferable that it is a straight or branched unsubstituted alkyl group having 12 to 24 carbon atoms.
[0096] Examples of monomers having one (meth)acrylate group in one molecule include lauryl (meth)acrylate, isostearyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-decyl tetradecyl (meth)acrylate, etc.
[0097] R 2 is a hydrogen atom or a methyl group, and it is preferable that it be a methyl group.
[0098] Examples of monomers having two or more (meth)acrylate groups in one molecule include hexanediol di(meth)acrylate, butanediol di(meth)acrylate (1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate), ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.
[0099] As a monomer having two or more (meth)acrylate groups in one molecule, from the perspective of compatibility of heat resistance and flexibility, it is preferable to have a compound having two and / or three (meth)acrylate groups in one molecule, more preferable to have a compound having two (meth)acrylate groups in one molecule, and even more preferable to have a compound represented by the following formula (2).
[0100] <Painting 4>
[0101]
[0102] R in the above equation (2) B1 represents an alkylene group having 1 to 5 carbon atoms, and R B2 and R B3 Each represents an independent hydrogen atom or a methyl group, and n represents an integer greater than or equal to 4.
[0103] R B1 The alkylene group having 1 to 5 carbon atoms represented by may be straight or branched.
[0104] R in terms of flexibility B1 The alkylene group represented by is preferably a straight-chain or branched-chain alkylene group having 2 to 5 carbon atoms, more preferably a straight-chain or branched-chain alkylene group having 2 to 4 carbon atoms, and even more preferably a branched-chain alkylene group having 3 or 4 carbon atoms.
[0105] R B2 and R B3 It is preferable that each is independently a methyl group.
[0106] It is preferable that n is 4 to 25, more preferable that it is 4 to 10, and even more preferable that it is 4 to 8.
[0107] R in Equation (2) in terms of flexibility and shape stability B1 is a straight or branched alkylene group having 2 to 5 carbon atoms (more preferably, a straight or branched alkylene group having 2 to 4 carbon atoms, and more preferably, a branched alkylene group having 3 or 4 carbon atoms), and R B2 and R B3 It is preferable that is a methyl group, and n is 4 to 25 (more preferably 4 to 10, and even more preferably 4 to 8).
[0108] The content of the monomer (B) having a (meth)acryloyl group is preferably 1% to 10% by mass with respect to the total mass of the composition, and more preferably 2% to 8% by mass.
[0109] A monomer (B) having a (meth)acryloyl group may be included in the composition as a single type or in two or more types.
[0110] In some embodiments, the monomer (B) having a (meth)acryloyl group preferably comprises at least one selected from monomers having one (meth)acrylate group in one molecule and at least one selected from monomers having two or more (meth)acrylate groups in one molecule.
[0111] The content ratio (A:B) of monomer A having one (meth)acrylate group in one molecule and monomer B having two or more (meth)acrylate groups in one molecule is preferably 99.5:0.5 to 95:5 on a mass basis and more preferably 99:1 to 97:3 in terms of the hardness and curing speed of the cured product.
[0112] The monomer (B) having a (meth)acryloyl group is preferably a monomer with a molecular weight of less than 1,000.
[0113] In the present disclosure, a monomer refers to a polymerizable compound with a molecular weight of less than 1,000, and a polymerizable polymer refers to a polymerizable compound with a weight average molecular weight (Mw) of 1,000 or more.
[0114] In this disclosure, the concept of "polymerizable polymer" also includes so-called oligomers.
[0115] <Polymerization Initiator (C)>
[0116] The curable composition related to the present disclosure comprises a polymerization initiator (C).
[0117] As a polymerization initiator (C), a known thermal polymerization initiator, a known photopolymerization initiator, etc., which is a compound that generates polymerization initiation species such as radicals and cations by energy of light, heat, or both, can be appropriately selected and used.
[0118] As for the polymerization initiator (C), a radical polymerization initiator is preferred in terms of the reactivity of the monomer (B) having a (meth)acryloyl group, a peroxide that generates free radicals by heat is more preferred, and an organic peroxide that generates free radicals by heat is even more preferred.
[0119] Organic peroxides include isobutyl peroxide, α, α'-bis(neodecanoylperoxy)diisopropylbenzene, cumyl peroxyneodecanoate, di-n-propylperoxydicarbonate, di-s-butylperoxydicarbonate, 1,1,3,3-tetramethylbutylperoxyneodecanoate, bis(4-t-butylcyclohexyl)peroxydicarbonate, 1-cyclohexyl-1-methylethylperoxyneodecanoate, di-2-ethoxyethylperoxydicarbonate, di(ethylhexyl)peroxydicarbonate, t-hexylperoxyneodecanoate, dimethoxybutylperoxydicarbonate, di(3-methyl-3-methoxybutyl)peroxydicarbonate, and t-butylperoxyneodecanoate. t-hexyl peroxypivalate, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, succinic peroxide, 2,5-dimethyl-2,5-di(2-ethylhexanoyl)hexane, 1-cyclohexyl-1-methylethylperoxy-2-ethylhexanoate, t-hexyl peroxy-2-ethylhexanoate, 4-methylbenzoyl peroxide, t-butylperoxy-2-ethylhexanoate, m-tornoylbenzoyl peroxide, benzoyl peroxide, t-butylperoxyisobutylate, 1,1-bis(t-butylperoxy)2-methylcyclohexane, 1,1-Bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-Bis(t-hexylperoxy)cyclohexane, 1,1-Bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-Bis(t-butylperoxy)cyclohexanone, 2,2-Bis(4,4-dibutylperoxycyclohexyl)propane, 1,1-Bis(t-butylperoxy)cyclododecane, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleic acid, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2,5-dimethyl-2,5-di(m-toluoylperoxy)hexane, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl carbonate, t-hexylperoxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxyacetate, 2,2-bis(t-butylperoxy)butane, t-butylperoxybenzoate, n-butyl-4,Examples include 4-bis(t-butylperoxy)valerate, di-t-butylperoxyisophthalate, α,α'bis(t-butylperoxy)diisopropylbenzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-butyl peroxide, p-menethane hydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexine, diisopropylbenzene hydroperoxide, t-butyltrimethylsilyl peroxide, 1,1,3,3-tetramethylbutylhydroperoxide, cumene hydroperoxide, t-hexyl hydroperoxide, t-butyl hydroperoxide, benzoyl peroxide, lauroyl peroxide, etc.
[0120] Among these, from the perspective of reactivity, it is preferable that the organic peroxide be at least one compound selected from the group consisting of benzoyl peroxide, t-butylperoxy-2-ethylhexyl carbonate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, and cumene hydroperoxide.
[0121] -content-
[0122] The content of the polymerization initiator (C) is preferably 0.5 parts by mass or more and 10 parts by mass or less, with respect to 100 parts by mass of the monomer (B) having a (meth)acryloyl group, and more preferably 0.5 parts by mass or more and 4 parts by mass or less.
[0123] <Dispersant(D)>
[0124] The curable composition related to the present disclosure includes a dispersant (D).
[0125] There are no specific restrictions on dispersants, and examples include anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, polymeric surfactants, alcohols, compounds having carboxyl groups such as fatty acids, metal soaps, fatty acid oligomer compounds, fluorinated surfactants, boron surfactants, etc.
[0126] As a dispersant (D), it is preferable to be at least one compound selected from the group consisting of nonionic surfactants, compounds having carboxyl groups, and metal soaps.
[0127] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, glycerin fatty acid esters, polyoxyethylene glycerin fatty acid esters, polyglycerin fatty acid ethers, polyglycerin fatty acid ethers, polyglycerin monoalkyl ethers, sucrose fatty acid esters, polyoxyethylene alkylamines, polyethylene glycol polypropylene glycol block copolymers, acetylene glycol, and polyoxyethylene adducts of acetylene glycol.
[0128] The compound having a carboxyl group is not particularly limited and may be a fatty acid having one carboxyl group and a hydrocarbon group in one molecule, or a compound having two or more carboxyl groups in one molecule. In some embodiments, a compound having a carboxyl group is more preferred as the dispersant (D), and a fatty acid is even more preferred.
[0129] Examples of compounds having a carboxyl group include aromatic carboxylic acids and fatty acids having an aliphatic hydrocarbon group with 12 to 22 carbon atoms.
[0130] Fatty acids having an aliphatic hydrocarbon group with 12 to 22 carbon atoms include stearic acid, oleic acid, palmitic acid, myristic acid, lauric acid, etc.
[0131] In addition, compounds having carboxyl groups include polycarboxylic acids having two or more carboxyl groups in one molecule (i.e., polycarboxylic acids) such as oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, and adipic acid; polycarboxylates such as alkylamine salts and alkylammonium salts of polycarboxylic acids; polycarboxylic acid polyaminoamides; polycarboxylate sodium salts; polycarboxylate ammonium salts; and polycarboxylate aminoalcohol salts; and polycarboxylic acid copolymers.
[0132] Examples of polycarboxylic acid compounds include alkylamine salts, alkylammonium salts, polycarboxylic acid polyaminoamides, sodium polycarboxylate salts, ammonium polycarboxylate salts, and amino alcohol polycarboxylate salts.
[0133] Examples of metal soaps include metal salts of higher fatty acids such as calcium stearate, potassium oleate, and calcium oleate.
[0134] In terms of flexibility, the dispersant (D) preferably comprises at least one compound selected from the group consisting of polyglycerin monoalkyl ether compounds, compounds having carboxyl groups, and metal soaps, more preferably comprises at least one compound selected from the group consisting of polyglycerin monoalkyl ether compounds and fatty acids having aliphatic hydrocarbon groups having 12 to 22 carbon atoms, and more preferably comprises at least one compound selected from the group consisting of polyglycerin monoalkyl ether compounds and compounds having unsaturated hydrocarbon groups having 18 to 22 carbon atoms.
[0135] -content-
[0136] The content of the dispersant (D) is preferably 0.1 parts by mass or more and 3 parts by mass or less per 100 parts by mass of the thermally conductive filler (A), more preferably 0.1 parts by mass or more and 1 part by mass or less, and particularly preferably 0.2 parts by mass or more and 0.8 parts by mass or less.
[0137] <Plasticizer(E)>
[0138] The curable composition related to the present disclosure preferably includes a plasticizer (E).
[0139] There are no specific limitations on the plasticizer (E), and examples include polymers used as plasticizers, fatty acid ester compounds having unsaturated hydrocarbon groups, aromatic carboxylic acid ester compounds, and oils containing fatty acids having unsaturated hydrocarbon groups and aromatic carboxylic acids.
[0140] In the present disclosure, "polymer" means a compound having a weight average molecular weight (Mw) of 1,000 or more.
[0141] In this disclosure, the concept of "polymer" includes so-called oligomers.
[0142] Examples of polymers include acrylic polymers, polyester polymers, polyurethane polymers, and silicone polymers, but acrylic polymers are preferred in terms of heat resistance and flexibility.
[0143] Polymers used as plasticizers include, for example, acrylic polymers, polyester polymers, polyurethane polymers, and silicone polymers; however, acrylic polymers are preferred in terms of heat resistance and flexibility.
[0144] As for the acrylic polymer, it is desirable to include constituent units that form acrylic acid esters from the perspective of heat resistance.
[0145] As for the (meth)acrylate ester, alkyl (meth)acrylate is preferred. Examples of (meth)acrylate esters include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and isobutyl (meth)acrylate.
[0146] In addition, alkyl acrylates can be non-functional alkyl acrylates, and may have functional groups such as carboxyl groups, hydroxyl groups, etc.
[0147] It is preferable that the functional group of the alkyl acrylate be a hydroxyl group.
[0148] Acrylic polymers are classified according to the following formula (P AC It may be a polymer having a structure represented by ).
[0149] <Painting 5>
[0150]
[0151] The above equation (P AC ) among R P represents a hydrogen atom or an alkyl group.
[0152] The above equation (P AC The alkyl group in ) may have a substituent. Examples of substituents include carboxyl groups, hydroxyl groups, amino acid groups, etc. As substituents, carboxyl groups or hydroxyl groups are preferred, and hydroxyl groups are more preferred.
[0153] As for the alkyl group, a saturated alkyl group is preferred, and an alkyl group having 1 to 4 carbon atoms is more preferred.
[0154] A curable composition related to the present disclosure comprises a plasticizer (E), and when the plasticizer (E) is a polymer, it is preferable that the polymer has a glass transition temperature of -20°C or lower for the sake of heat resistance and flexibility, and more preferably that the polymer has a glass transition temperature of -20°C or lower.
[0155] A curable composition related to the present disclosure comprises a plasticizer (E), and when the plasticizer (E) is a polymer, it is preferable that the polymer has a glass transition temperature of -90°C or higher and -20°C or lower for the sake of heat resistance and flexibility, and it is more preferable that the polymer has a glass transition temperature of -90°C or higher and -20°C or lower.
[0156] The glass transition temperature (Tg) of a polymer is determined by examining the inflection point of the DSC curve measured using a differential thermal analysis (DSC).
[0157] Examples of fatty acid ester compounds having unsaturated hydrocarbon groups include ester compounds such as palmitoleic acid, oleic acid, linoleic acid, and linolenic acid.
[0158] Examples of aromatic carboxylic acid ester compounds include ester compounds such as phthalic acid, terephthalic acid, benzoic acid, and trimellitic acid.
[0159] When the curable composition related to the present disclosure comprises a plasticizer (E), for the sake of high-temperature stability, it is preferable that the plasticizer (E) comprises an aromatic carboxylic acid ester compound, and more preferable that it comprises a trimellitic acid ester.
[0160] -content-
[0161] When the curable composition related to the present disclosure includes a plasticizer (E) (in the case where two or more types of plasticizers (E) are included, the total amount), from the perspective that heat resistance and flexibility are compatible, the content of the plasticizer (E) is preferably 10 parts by mass or more and 60 parts by mass or less per 100 parts by mass of a monomer (B) having a (meth)acryloyl group, more preferably 20 parts by mass or more and 50 parts by mass or less, and even more preferably 30 parts by mass or more and 45 parts by mass or less.
[0162] Plasticizer (E) may be included as a single type or two or more types.
[0163] Other Additives
[0164] The curable composition related to the present disclosure may, as needed, include a thermally conductive filler (A), a compound having (meth)acryloyl groups (B), a polymerization initiator (C), a dispersant (D), and a plasticizer (E), as well as other components (hereinafter also referred to as “other additives”).
[0165] Other additives such as reducing agents (F), antioxidants, corrosion inhibitors, rust inhibitors, and rheology control agents (viscosity modifiers) may be appropriately incorporated.
[0166] The above additives may be used alone or in combination of two or more types.
[0167] << Reducing agent (F)>>
[0168] The curable composition related to the present disclosure may contain a reducing agent (F) as needed.
[0169] When applying the curable composition related to the present disclosure to the two-component curable composition described below, it is preferable to include a reducing agent (F) in one of the compositions. By adding the reducing agent (F), the decomposition of the polymerization initiator (C) (e.g., peroxide) is facilitated, and the polymerization reaction proceeds easily even under low temperature conditions.
[0170] As for the reducing agent (F), there are no special restrictions as long as it can promote the decomposition of the polymerization initiator (C), and any known reducing agent used in combination with the polymerization initiator may be used. However, from the perspective of promoting the decomposition of the polymerization initiator (C), it is preferable that it be a metal compound-based reducing agent.
[0171] Examples of metal compound-based reducing agents include tin(II) oxide, dioctyltin dilaurate, dibutyltin dilarurate, dibutyltin diacetate, zinc naphthenate, antimony trichloride, potassium oleate, sodium O-phenylphenate, bismuth nitrate, ferric chloride, tetra-n-butyltin, tetra(2-ethylhexyl)titanate, cobalt 2-ethylhexoate, and ferric 2-ethylhexoate.
[0172] -content-
[0173] When the curable composition related to the present disclosure includes a reducing agent (F), in terms of curing speed, the content of the reducing agent (F) is preferably 0.5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of a monomer (B) having a (meth)acryloyl group, and more preferably 2 parts by mass or more and 9 parts by mass or less.
[0174] The reducing agent (F) can be used as a single type or in combination with two or more types.
[0175] <<Antioxidant>>
[0176] Examples of antioxidants include phenolic antioxidants, amine-based antioxidants, and phosphite-based antioxidants.
[0177] << Corrosion Inhibitor >>
[0178] Examples of corrosion inhibitors include benzotriazole, triltriazole, thiadiazole, and benzimidazole.
[0179] Rust Inhibitor
[0180] Examples of rust inhibitors include metal sulfonic acid salt compounds and sorbitan compounds.
[0181] << Rheology Control Agents >>
[0182] In the present disclosure, a rheology control agent refers to an additive that imparts non-Newtonian properties with respect to changes in shear rate. Specifically, the rheology control agent is an additive that imparts flow characteristics in which shear viscosity is increased in the low shear rate range while shear viscosity is lowered in the high shear rate range.
[0183] Rheology control agents can be inorganic or organic compounds. Examples of inorganic rheology control agents include fumed silica, bentonite, mica, and kaolin.
[0184] In addition, organic compound-based rheology control agents include urea-modified polymers, urethane-modified polymers, castor oil wax, polyethylene wax, polyamide wax, fatty acid amide wax, etc.
[0185] Among these, inorganic compound-based rheology control agents are preferred as rheology control agents, fumed silica or bentonite are more preferred, and bentonite is even more preferred. When fumed silica is used, it is preferable to make the surface hydrophobic by a silane coupling agent or other surface modifier. Also, when bentonite is used, organified bentonite organically modified by a quaternary ammonium salt or other organic modifier is preferably used.
[0186] The content of rheology control agents has no special limitations and can be set appropriately.
[0187] [Physical properties of the curable composition]
[0188] With respect to viscoelasticity, handling properties, and degassing properties, the degree of diffusion of the curable composition related to the present disclosure is preferably 100 to 500, more preferably 260 to 340, and even more preferably 280 to 310.
[0189] The degree of diffusion can be determined by inserting 0.05 mL of a sample (curable composition before curing) between two acrylic plates in an environment of 25°C, applying a load of 100 g for 5 seconds to compress the sample, measuring the diffusion diameter of the sample in millimeters, and multiplying the value obtained by subtracting 1 from this measurement by 20.
[0190] Diffusion rate = (Measurement - 1) × 20
[0191] [Curable composition form]
[0192] The curable composition related to the present disclosure is preferably a one-component curable composition that uses one type of curable composition when applied to a substrate, heating element, etc. The curable composition related to the present disclosure may be a two-component curable composition that uses a mixture of two types of curable compositions.
[0193] [Method for preparing a curable composition]
[0194] The method for preparing the curable composition related to the present disclosure is not particularly limited and is not specifically restricted. The curable composition related to the present disclosure may be prepared, for example, by the following method.
[0195] In one embodiment, a curable composition related to the present disclosure is obtained by introducing a thermally conductive filler (A), a polymerization initiator (C) and a dispersant (D), and optionally a plasticizer (F) and other additives into a stirring vessel and stirring and mixing.
[0196] In addition, known stirrers, etc., may be used for stirring and mixing.
[0197] In the method for preparing a curable composition, when adding other additives, stirring is sufficient for a time during which the additives can be dissolved or dispersed. The other additives may be added to the stirring vessel together with the components other than the other additives, or added to the stirring vessel after the components other than the other additives have been mixed.
[0198] (hardened material)
[0199] The cured product related to the present disclosure is a cured product of the curable composition related to the present disclosure. The method for curing the curable composition is not limited and can be appropriately selected from commonly used methods. Examples of curing methods include irradiation with active energy rays and heating, and curing by heating is preferred.
[0200] When curing by heating, the heating temperature is preferably 60°C or higher, and more preferably 70°C or higher. In addition, the heating time is preferably 1 minute to 120 minutes.
[0201] In addition, the above-mentioned curing composition may be cured by reacting with moisture in the air or cured at room temperature.
[0202] Regarding the thermal conductivity of the cured article related to the present disclosure, it is preferable to have a thermal conductivity of 0.5[W / m·K] to 50[W / m·K] with respect to flexibility, shape stability, and inhibition of changes in thermal conductivity, 1[W / m·K] to 20[W / m·K], and more preferable to have a thermal conductivity of 3[W / m·K] to 20[W / m·K].
[0203] Regarding the flexibility of the cured product related to the present disclosure, it is preferable that the Shore hardness be 100 or less and more preferable that it be 85 or less in terms of stress relief for parts surrounding the cured product.
[0204] Likewise, it is preferable that the Aska C hardness be 100 or less, more preferable that it be 85 or less, and even more preferable that it be 75 or less.
[0205] The flexibility of the cured product related to the present disclosure is obtained by Shore OO hardness in accordance with ASTM D2240 and Aska C hardness in accordance with JIS K 7312:1996.
[0206] <Uses>
[0207] The curable composition related to the present disclosure can preferably be used as a TIM that fills, for example, a recess formed in a substrate (i.e., a gap between a heating element and a heat dissipation element).
[0208] The curable composition related to the present disclosure has excellent oil-removing properties, so the desired quality can be maintained over a long period. In addition, the curable composition related to the present disclosure has excellent viscosity and thermal conductivity, so the manufacturability and thermal conductivity of the resulting cured product are also excellent.
[0209] A cured product obtained from a curable composition related to the present disclosure has excellent flexibility, shape stability, and thermal conductivity, and thus has excellent conformability to a coating surface, such as a concave portion formed on a substrate, allowing for efficient heat dissipation even when there are components of different heights on the substrate. In addition, the curable composition related to the present disclosure can follow even the irregularities of fine materials on the substrate, thereby allowing for efficient heat dissipation, and can also be preferably applied as a gap filler in that it has excellent conformability to a coating surface in response to temperature fluctuations.
[0210] <Example>
[0211] Hereinafter, the curable composition and cured product related to the present disclosure will be specifically described by way of examples. Furthermore, the curable composition and cured product related to the present disclosure are not limited to these examples.
[0212] (Examples 1–10 and Comparative Examples 1–6)
[0213] Each raw material was mixed in the amounts listed in Table 1 or Table 2, and a curable composition was prepared by mixing using a rotating / revolutionary mixer (Shinky Co., Ltd., product name: Awatori Neritaro ARV-310) at 2,000 rpm (revolution sper minute) and 2 minutes at atmospheric pressure.
[0214] The content (mass%) of thermal conductive fillers A, B, and C in the total amount (100 mass%) of thermal conductive filler (A) is shown in Table 3.
[0215] The following evaluations were performed using the curable compositions prepared in Examples 1 to 10 and Comparative Examples 1 to 6. The results are shown in Tables 1 and 2.
[0216] -evaluation-
[0217] Meteor Shower
[0218] 200g of the curable composition prepared above was sealed in a receiving container (High Resist container, product name: BHR-150, manufactured by Kinki Container Co., Ltd.) and stored for 14 days, 28 days, or 60 days under an environment of 10℃.
[0219] For each curable composition after a predetermined storage period, the mass [g] was measured after removing the liquid component that had separated from the composition, and the oil-free rate [%] was calculated based on the following formula A.
[0220] (Equation A)
[0221] Delay Rate [%] = (Amount of Delayed Component [g] / Amount of Liquid Component Contained in Curable Composition Before Storage [g]) × 100
[0222] In this evaluation, the curable composition was assessed as having excellent oil-reducing properties when the oil-reducing rate [%] shown below was determined according to each storage period.
[0223] (Storage period) (Downward yield [%])
[0224] 0.5% or less for 14 days
[0225] 1.0% or less for 28 days
[0226] 1.5% or less for 60 days
[0227] Viscosity
[0228] For the curable composition prepared above, the shear viscosity η [Pa·s] at 25°C was measured using a dynamic viscoelasticity measuring device (manufactured by Anton Paar, product name: MCR 101).
[0229] A PP25 parallel plate (diameter 25 mm, manufactured by Anton Paar) was used as a jig for the curable composition to be measured.
[0230] The measurement was carried out by measuring the shear viscosity η [Pa·s] at each shear rate of 0.01 [1 / s], 0.1 [1 / s], 1 [1 / s], 10 [1 / s], and 100 [1 / s].
[0231] <Thermal Conductivity [W / m·K]>
[0232] Thermal conductivity was measured in accordance with ASTM D5470.
[0233] A curable composition molded to have dimensions of 10mm × 10mm × 1mm (width × length × height (thickness)) is clamped at the top and bottom with 10mm × 10mm copper plates, and after curing under conditions of 80°C for 30 minutes in an N2 purging atmosphere, the thermal resistance (unit: K·cm²) is measured using a thermal resistance measuring device (manufactured by Tsukubarika Seiki Co., Ltd., product name: Thermal Resistance Measuring Device). 2 / W) was measured and converted into thermal conductivity.
[0234] In this evaluation, thermal conductivity was evaluated as excellent when it was 3 W / m·K or higher.
[0235] <Extent of Spread>
[0236] The degree of diffusion was determined by inserting 0.05 mL of the sample (curable composition before curing) between two acrylic plates in an environment of 25°C, applying a load of 100 g for 5 seconds to compress the sample, measuring the diffusion diameter of the sample in millimeters, and multiplying the value obtained by subtracting 1 from this measurement by 20.
[0237] <Hardness: Shape Stability>
[0238] - Flexibility after curing: Shore OO hardness (sample thickness: 6mm)-
[0239] The flexibility of the cured product of the curable composition was measured in accordance with ASTM D2240.
[0240] The curable composition was molded into a 50mm × 20mm × 6mm (thickness 6mm) and cured under conditions of 80℃ for 30 minutes in an N2 purging atmosphere, after which the Shore OO hardness was measured using a durometer (product name: GS-754G, manufactured by Techlock Co., Ltd.) and an Aska rubber hardness tester.
[0241] -Flexibility after curing: Aska C hardness (sample thickness: 6mm)-
[0242] The flexibility of the cured product of the curable composition was measured in accordance with JIS K 7312:1996.
[0243] The curable composition is molded into a 50mm × 20mm × 6mm (thickness 6mm) shape, N 2 After curing under a fuzzy atmosphere at 80°C for 30 minutes, the Aska C hardness was measured using an Aska rubber hardness tester type C (manufactured by Polymer Instruments Co., Ltd.).
[0244]
[0245]
[0246]
[0247] The detailed contents of each component listed in Tables 1 and 2 are as follows.
[0248] The '-' in Tables 1 and 2 indicates that the corresponding component is not included.
[0249] 'Filling rate, [mass%]' in Tables 1 and 2 represents the ratio of the total mass of the thermally conductive filler (A) to the total mass of the composition.
[0250] In Table 3, '%' represents 'mass%'.
[0251] << Monomer with (meth)acryloyl group (B)>
[0252] · ITEC: 2-Decyltetradecyl Methacrylate; Manufactured by Shinnakamura Chemical Industry Co., Ltd.
[0253] · Light Ester L: Lauryl Methacrylate; Manufactured by Kyoeisha Chemical Co., Ltd., Product Name; LMA
[0254] · 9PG (Difunctional Monomer): Polypropylene Glycol Dimethacrylate; Manufactured by Shinnakamura Chemical Industry Co., Ltd., Product Name: 9PG
[0255] << Plasticizer(E) >>
[0256] · C-880: Adekasizer C-880 (Product Name); Trimellitic acid mixed straight-chain alkyl ester; Manufactured by ADEKA Co., Ltd.
[0257] <<Polymerization Initiator (C)>>
[0258] · Perocta-O: 1,1,3,3-Tetramethylbutylperoxy-2-ethylhexanoate; Manufactured by Nityu Co., Ltd.
[0259] << Dispersant (D) >>
[0260] · Oleic acid: Manufactured by Nippon Yuji Co., Ltd., Product name: Oleic acid
[0261] <<Thermal conductive filler (A)>>
[0262] (Zinc oxide)
[0263] · Zinc Oxide Type 1: Volume average particle diameter; 0.6μm, Manufactured by Sakai Chemical Industry Co., Ltd.
[0264] · Calcined Zinc Oxide 1: Volume average particle diameter; 4μm, Manufactured by Haksu Tech Co., Ltd.
[0265] · Calcined Zinc Oxide 2: Volume average particle diameter; 11μm, Manufactured by Haksu Tech Co., Ltd.
[0266] · Calcined Zinc Oxide 3 (Surface-treated product): Silane coupling agent treated, volume average particle diameter; 12μm, manufactured by Haksu Tech Co., Ltd.
[0267] · Calcined zinc oxide IV: Volume average particle diameter; 19μm, manufactured by Haksu Tech Co., Ltd.
[0268] (Magnesium oxide)
[0269] ·RF-10CS-SC: Product name, volume average particle diameter; 10μm, manufactured by Ube Materials Co., Ltd.
[0270] (Aluminum oxide)
[0271] ·AA-10: Product Name: Volume Average Particle Diameter; 13.5μm, Manufactured by Sumitomo Chemical Corporation)
[0272] As shown in the results of Tables 1 and 2, it can be seen that the curable compositions of Examples 1 to 10 have superior oil-repellent properties compared to the curable compositions of Comparative Examples 1 to 6.
[0273] Accordingly, the curable composition and cured product related to the present disclosure can be preferably used as gap fillers.
[0274] The disclosure of Japanese Patent Application No. 2021-061631, filed on March 31, 2021, is incorporated herein by reference in its entirety. All documents, patent applications, and technical specifications described herein are incorporated herein by reference to the same extent as if each document, patent application, and technical specification were specifically and individually described by reference.
Claims
Claim 1 A curable composition comprising a thermally conductive filler (A) having a volume-average particle diameter of 0.3 μm or more and less than 1 μm, a thermally conductive filler B having a volume-average particle diameter of 1 μm or more and less than 10 μm, and a thermally conductive filler C having a volume-average particle diameter of 10 μm or more and less than 15 μm, a monomer (B) having a (meth)acryloyl group, a polymerization initiator (C), and a dispersant (D), wherein, based on the total mass of the thermally conductive filler (A), the content X of the thermally conductive filler A is 18.60 mass% to 40 mass%, the content Y of the thermally conductive filler B is 16.88 mass% to 40 mass%, and the content Z of the thermally conductive filler C is 20 mass% to 60 mass%. Claim 2 A curable composition according to claim 1, wherein the thermally conductive filler (A) comprises at least one selected from zinc oxide, magnesium oxide, and aluminum oxide. Claim 3 In paragraph 2, the heat-conductive filler (A) comprises zinc oxide, forming a curable composition. Claim 4 A curable composition according to claim 1, wherein the thermally conductive filler (A) is a surface-treated thermally conductive filler. Claim 5 A curable composition according to claim 1, wherein the monomer (B) comprises a compound represented by the following formula (1). <Formula 1> R in the above equation (1) 1 represents an alkyl group having 1 to 50 carbon atoms, and R 2 represents a hydrogen atom or a methyl group. Claim 6 A curable composition according to claim 1, wherein the monomer (B) comprises a compound represented by the following formula (2).<Formula 2> R in the above equation (2) B1 represents an alkylene group having 1 to 5 carbon atoms, and R B2 and R B3 Each represents independently a hydrogen atom or a methyl group, and n represents an integer greater than or equal to 4. Claim 7 A cured product made of a curable composition as described in any one of paragraphs 1 to 6.
Citation Information
Patent Citations
Curable composition, cured product thereof, and optical member
KR1020170125318A
Organic-inorganic composite particles and their manufacturing method, thermally conductive filler and thermally conductive resin composition and their manufacturing method
KR1020190085167A
Compounds, potential antioxidants, compositions, curing agents and methods for producing cured products
KR1020200058327A
Curable composition, curable composition set, heat storage material, and article
KR1020210010446A
Thermally conductive resin composition
US10640631B2